The effects of age on the pharmacokinetics and pharmacodynamics of single oral doses of benazepril and enalapril. - Macdonald, N J (1993)
1. Eighteen healthy, normotensive subjects (nine young and nine elderly) participated in a double-blind, 3-way, crossover study to compare aspects of the pharmacokinetics and pharmacodynamics of single oral doses of 10 mg benazepril, 10 mg enalapril and placebo. 2. The hypotensive effect was similar after both drugs but the absolute reductions were greater in the elderly who had higher initial levels of blood pressure. 3. The AUCs for both benazeprilat and enalaprilat were higher in the elderly but by a significantly greater amount for enalaprilat (+ 113% vs 40%; P < 0.01). 4. The AUCs for both drugs tended to be highest in subjects with the lowest creatinine clearance. 5. The changes in kinetics and dynamics observed in the elderly after benazepril are qualitatively similar to those with other ACE inhibitors. The clinical significance of the quantitative differences requires further investigation.